2011
DOI: 10.1016/j.pnpbp.2010.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mood stabilizers on adult dentate gyrus-derived neural precursor cells

Abstract: Neurogenesis in the adult dentate gyrus (DG) is considered to be partly involved in the action of mood stabilizers. However, it remains unclear how mood stabilizers affect neural precursor cells in adult DG. We have established a culture system of adult rat DG-derived neural precursor cells (ADP) and have shown that lithium, a mood stabilizer, and dexamethasone, an agonist of glucocorticoid receptor, reciprocally regulate ADP proliferation. Neurogenesis constitutes not only proliferation of neural precursor ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 55 publications
1
36
0
Order By: Relevance
“…In hippocampal neural progenitor/precursor cell cultures, lithium increased proliferation, decreased apoptosis, and selectively 1437 www.chinaphar.com Wang ZF et al Acta Pharmacologica Sinica npg enhanced the neuronal differentiation of these cells [81,82] . Lithium treatment enhanced ERK and CREB phosphorylation in cultured hippocampal neural progenitor cells; PD98059, a MEK inhibitor, significantly decreased lithium-induced neuronal subtype differentiation [82] .…”
Section: Pro-neurogenic Effectsmentioning
confidence: 99%
“…In hippocampal neural progenitor/precursor cell cultures, lithium increased proliferation, decreased apoptosis, and selectively 1437 www.chinaphar.com Wang ZF et al Acta Pharmacologica Sinica npg enhanced the neuronal differentiation of these cells [81,82] . Lithium treatment enhanced ERK and CREB phosphorylation in cultured hippocampal neural progenitor cells; PD98059, a MEK inhibitor, significantly decreased lithium-induced neuronal subtype differentiation [82] .…”
Section: Pro-neurogenic Effectsmentioning
confidence: 99%
“…To estimate the effects of drugs on the number of cells, we used Alamar Blue assay (Invitrogen) as in the cases of our previous studies [7,8]. GDNF and/or stattic.…”
Section: Cell Countingmentioning
confidence: 99%
“…GDNF and/or stattic. After 7 days, immunocytochemistry was performed with our previour studies [7,8]. Primary antibodies were used at the following concentrations: mouse anti-nestin anti-phospho-STAT3 (Tyr705) antibody (1:1000; Cell Signaling) as described in our past study (Boku et al, 2009).…”
Section: Cell Countingmentioning
confidence: 99%
See 1 more Smart Citation
“…Boku et al (2011) demonstrated that lithium and valproate, but not carbamazepine and lamotrigine, prevented the decrease in dentate gyrus-derived neural precursor cell proliferation induced by dexamethasone. However, all four mood stabilizers blocked apoptosis of dentate gyrusderived neural precursor cells.…”
Section: The Effect Of Mood Stabilizers On Stress-induced Inhibition mentioning
confidence: 96%